2022
DOI: 10.1039/d2cp03364j
|View full text |Cite
|
Sign up to set email alerts
|

Substrate effects on the speed limiting factor of WSe2 photodetectors

Abstract: We investigate the time-resolved photoelectric response of WSe2 crystals on glass and flexible polyimide substrates to determine the effect of a changed dielectric environment on the speed of the photodetectors....

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…The WSe 2 transition metal dichalcogenide detectors were prepared as reported elsewhere using Scotch tape exfoliation of TMDC flakes onto lithographically fabricated electrodes (WSe 2 : 2 nm Ti/10 nm Au, MoS 2 : 4 nm Ti/20 nm Au, 5 μm × 80 μm, finger width = 10 μm, flake thickness WSe 2 : 30 nm, flake thickness MoS 2 : 110 nm). In contrast, the MoS 2 detectors were fabricated by exfoliating the TMDC first before performing lithography onto the flakes.…”
Section: Methodsmentioning
confidence: 99%
“…The WSe 2 transition metal dichalcogenide detectors were prepared as reported elsewhere using Scotch tape exfoliation of TMDC flakes onto lithographically fabricated electrodes (WSe 2 : 2 nm Ti/10 nm Au, MoS 2 : 4 nm Ti/20 nm Au, 5 μm × 80 μm, finger width = 10 μm, flake thickness WSe 2 : 30 nm, flake thickness MoS 2 : 110 nm). In contrast, the MoS 2 detectors were fabricated by exfoliating the TMDC first before performing lithography onto the flakes.…”
Section: Methodsmentioning
confidence: 99%
“…21 For bulk WSe 2 , we found that the dielectric constant of the substrate alters not only the response time but also the speed- 3a). 3 For the detectors on glass, the response time is slower than the RC constant, presumably now limited due to drift limitation as a consequence of a shrunken depletion layer induced by the higher dielectric screening (Figure 3b). The maximal achieved bandwidth is 2.6 MHz.…”
Section: Substrate Effectsmentioning
confidence: 99%
“…Glass has a larger dielectric constant of 4.5–8, in comparison to the weaker screening on polyimide with 3.7. For polyimide, the WSe 2 detectors are faster and are limited by the RC time (Figure a) . For the detectors on glass, the response time is slower than the RC constant, presumably now limited due to drift limitation as a consequence of a shrunken depletion layer induced by the higher dielectric screening (Figure b).…”
Section: Speed-limiting Factors To the Extrinsic Photoresponsementioning
confidence: 99%
See 1 more Smart Citation
“…13 Many methods have been used in the search for ultrafast photodetectors based on nanomaterials: chemical doping, 14 heterojunction implementation, 15,16 photonic waveguide integration, 17 and small channel lengths, 18,19 to name a few. In addition, parameters such as the choice of substrate, 18,20 interface roughness, 21 electrode material, 10,22,23 and geometry 13,24,25 or environment 26,27 must be considered each time.…”
Section: Introductionmentioning
confidence: 99%